Satu Abad Nahdlatul Ulama dalam sebuah Qasidah Karya KH. Afifuddin Muhajir (Analisis Semiotika Riffaterre) - Lutfi, Mukhammad; Abdullah, Abdullah; Suparno, Darsita (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
The goal of this research is to uncover the true meaning of a Qasidah that employs symbols and indirect expression. The material object studied is Qasidah Nahdliyah Satu Abad Nahdlatul Ulama by KH. Afifuddin Muhajir, also known as Qasidah NSANU, which is a qasidah written to commemorate the centennial of Nahdlatul Ulama (NU) on 16 Rajab 1444 H (7 February 2023 AD) according to the Hijri calendar. The descriptive qualitative method with Riffaterre’s semiotic approach was used in this study. Riffaterre provides stages for understanding a poem’s full meaning, including heuristic reading, hermeneutic reading, determining models, variants, and matrices, and determining hyprograms. The study’s findings indicate that the Qasidah NSANU as a whole contains content about the history of NU’s founding, its role in maintaining Indonesian unity, and the figures who played a role in NU’s founding. This matrix was discovered after obtaining models in the form of words, phrases, and sentences. It is titled "a century of NU: the figure behind its founding and its attitude in maintaining Indonesian unity." The potential hypogram of the Qasidah’s creation is a response from the Qasidah’s creator’s gratitude for the hundred years of NU, which is then poured into the Qasidah’s text. Meanwhile, the actual hypogram was inspired by Hadlratus Shaykh Hasyim Asy’ari’s jargon "Hubbul Wathan minal iman," as well as the song "Subbanul Wathan," or more colloquially "ya lal Wathan," composed by KH. Abdul Wahab Chasbullah. مستلخص الهدف من هذا البحث هو الكشف عن المعنى الشامل للقصيدة التي تستخدم الرموز وعدم مباشرة التعبير. الموضوع المادي الذي تمت دراسته هو قصيدة نهضية في قرن واحد بنهضة العلماء (Qasidah Nahdliyah Satu Abad Nahdlatul Ulama) بقلم كياهي الهاج عفيف الدين مهاجر⸻المشار إليه فيما بعد باسم Qasidah NSANU، هي قصيدة تم تكوينها خصيصًا للترحيب بالذكرى المئوية لنهضة العلماء (NU) في 16 رجب 1444 هـ (7 فبراير 2023 م) والتي يتم حسابها على أساس التقويم الهجري. الطريقة المستخدمة في هذا البحث هي الطريقة الوصفية النوعية مع منهج ريفاتير السيميائي. يقدم ريفاتير مراحل لفهم المعنى الشامل للقصيدة أوالشعر، أي من خلال القراءة الاستكشافية، والقراءة التأويلية، وتحديد النماذج (model)، والنوع (varian) والمصفوف (matriks) ، وتحديد الهيبوجرام. تظهر نتائج الدراسة أن Qasidah NSANU أساسا لها معنى عن تاريخ تأسيس NU، ودورها في الحفاظ على الوحدة الإندونيسية ، وكذلك الشخصيات التي لها دور في تأسيس NU. والمصفوفة التي تم الحصول عليها هي " في قرن واحد بنهضة العلماء: الشخصيات وراء تأسيسها وموقفها في الحفاظ على الوحدة الإندونيسية"، تم العثور على هذه المصفوفة بعد الحصول على نماذج في شكل كلمات وعبارات وجمل. الهيبوجرام المحتمل لإنشاء هذه القصيدة هو استجابة من امتنان مؤلف القصيدة لمئات السنين من NU ، والتي يتم سكبها بعد ذلك في نص القصيدة. في هذه الأثناء، تم استلهام الهيبوجرام الفعلي من المصطلح "hubbul wathan minal iman" لحضرة الشيخ هاشم أشعاري، وكذلك أغنية "syubbanul wathan" أو الأكثر شهرة “ya lal wathan”من ألحان كياهي الحاج عبد الوهاب حسب الله. الكلمات المفتاحية: قصيدة؛ عفيف الدين مهاجر؛ نهضة العلماء؛ السيميائي